Benefit of salvage total pharyngolaryngoesophagectomy for recurrent locally advanced head and neck cancer after radiotherapy - Liu, Jie (Radiat Oncol, 2017)
BACKGROUND: The treatment modalities for recurrent locally advanced head and neck cancer failure after radiotherapy are limited with poor prognosis. Salvage supra-radical operation seems to be an option. It has not been established which patients will benefit from salvage total pharyngolaryngoesophagectomy. METHODS: We retrospectively reviewed 66 patients with previously irradiated recurrent T4 head and neck cancer who underwent salvage total pharyngolaryngoesophagectomy at our institution between January 2001 and June 2014. The clinical outcome and toxicities were analyzed. RESULTS: Flap loss occurred in 2 patients, and the incidence of fistulas and anastomosis strictures was 15.6% (10/66) and 13.6% (9/66), respectively. The median survival time of the entire cohort was 12 months. The interval between radiation and salvage surgery, and microscopic carotid artery invasion were identified as independent prognostic factors for overall survival. The 3-year overall survival rates of patients with (n = 33) and without (n = 33) risk factors were 9.1% and 47.2%, respectively (p = 0.007). A time interval between radiation and salvage surgery ≤6 months and previous concurrent chemotherapy or targeted therapy were risk factors for severe post-operative complications. CONCLUSIONS: Salvage total pharyngolaryngoesophagectomy is beneficial to selected patients with recurrent locally advanced head and neck cancer after radiotherapy.